دور الشمول المالي في تحقيق التنمية المستدامة في مصر (Journal of Economics and Management Research, 2022)
يحظى الشمول المالي بأهمية متزايدة خلال السنوات الأخيرة للدول المتقدمة والنامية على حد سواء، لذلك يهدف الباحث من خلال هذه الدراسة إلى دراسة إنعكاس الشمول المالي على التنمية المستدامة في مصر، وقد إعتمد الباحث في منهجيته على المنهج الوصفي التحليلي والمنهج الكمي بإتباع الاسلوب القياسي، وقد تم إختبار بعض مؤشرات الشمول المالي ممثلة في (فروع البنوك التجارية لكل 100 الف بالغ، صافي الائتمان، الادخار كنسبة من الناتج المحلي الاجمالي)، لبيان أثرها على نصيب الفرد من الناتج المحلي الاجمالي كمؤشر اقتصادي للتنمية المستدامة، وقد توصلت الدراسة إلى أن هناك علاقة إيجابية طردية بين مؤشري فروع البنوك التجارية، وصافي الائتمان على التنمية المستدامة في مصر، وعلاقة عكسية سلبية بين مؤشر الادخار على التنمية المستدامة في مصر. Financial inclusion is of increasing importance in recent years for both developed and developing countries, so the researcher aims through this study to study the implications of financial inclusion on sustainable development in Egypt. Testing some indicators of financial inclusion represented in (branches of commercial banks per 100,000 adults, net credit, savings as a percentage of GDP), to show their impact on per capita GDP as an economic indicator for sustainable development. The study concluded that there is a positive direct relationship Among the indicators of commercial bank branches, net credit on sustainable development in Egypt, and a negative inverse relationship between the indicator of total savings on sustainable development in Egypt.